Arabidopsis ACYL‐ACTIVATING ENZYME 9 (AAE9) encoding an isobutyl‐CoA synthetase is a key factor connecting branched‐chain amino acid catabolism with iso‐branched wax biosynthesis. Issue 6 (17th January 2022) - Li, Shipeng; Yang, Xianpeng; Huang, Haodong; Qiao, Rong; Jenks, Matthew A.; Zhao, Huayan; Lü, Shiyou
Summary: Iso ‐branched wax compounds are well known in plants, but their biosynthetic pathways are still mostly unknown. It has been speculated that branched waxes are derived from branched‐chain amino acid (BCAA) catabolism, but the evidence for this is very limited. Gas chromatography‐flame ionisation detection (GC‐FID) analysis revealed that mutations in two subunits of the branched‐chain ketoacid dehydrogenase (BCKDH) complex, a key enzyme complex in the degradation of BCAAs, significantly decreased the amounts of branched wax compounds, indicating that BCAA degradation may be integral to the synthesis of iso ‐branched wax. Substrate feeding studies further revealed that the metabolic precursor of iso ‐branched wax compounds is isobutyric acid (iBA), which is derived from valine degradation in Arabidopsis. We also isolated a novel mutant and found that its branched wax deficient phenotype could not be rescued by iBA. Map‐based cloning together with complementation analysis revealed that mutation in ACYL‐ACTIVATING ENZYME 9 ( AAE9 ) is responsible for this phenotype. Genetic and enzyme activity analysis demonstrated that AAE9 is located downstream of the BCAA degradation pathway, and that it activates iBA to isobutyryl‐CoA for use on branched wax synthesis. Taken together, our study demonstrates that AAE9 is a key factor connecting BCAA catabolism with branched wax biosynthesis.